Literature, landscape and toponymy: Sarmiento once again - Angueira, Anxo (Madrygal. Revista de Estudios Gallegos, 2014)
Since Middle Ages it is frequent in Galician literature the establishment of close links from authors (especially poets) with places and territories. In this relationship the toponym, that works as appropriation mark, is essential. In fact, in Contemporary Age, among other changes, the attempt of using the landscape, always with its toponyms, in a general strategy of liberation own of the literatures of subaltern nations is observed. Who first started the mentioned strategy and made use of toponyms weapon in its appropriation (sea inlet of Pontevedra) was Martín Sarmiento in his Coloquio (1746). While Rosalía (Iria Land) follows the Sarmiento’s line with Cantares gallegos (1863), Pondal (Bergantiños), in the XIXth century, with his Queixumes dos pinos (1886) and Uxío Novoneira (O Courel) in the XXth century, with Os eidos (1955) modulate strongly the appropriation strategy when they create their respective phonic landscapes in which toponym is again a fundamental axel.